Det umuliges kunst – Om Alenka Zupančič’ teori om komedien - Porsgaard, Kasper (Slagmark - Tidsskrift for idéhistorie, 2018)
The article presents the theory of comedy which has been developed by Alenka Zupančič’ in her book The Odd One In from 2008. The first part of the article shows how Zupančič’ approach to comedy is positioned within the field of classical philosophical theories on comedy and laughter; the second part seeks to clarify the two main sources of inspiration behind Zupančič’ theory: Hegel and Lacan. While the Hegelian theory provides an account of how comedy manages to present a conflict or short circuit in a universal order, the Lacanian theory provides a theory of ‘the impossible object’, also known as the petit objet a, which is seen to emerge in the place of conflict described by Hegel. The article thus argues that the fruitful combination of Hegel and Lacan is exactly what gives Zupančič’ theory of comedy its unique strength and significance.